Neither Chuckwagons, nor Saskatoons, and a Missing Marlboro Man: Postcolonialism, Regionalism and the Ineffable Canadian West - Pedro Miguel Carmona-Rodríguez, (Miscelánea: A Journal of English and American Studies, 2015)
Contemporary transnational and transcontinental trends of theory enable a mandatory analysis of how region and regionalism have been fundamental in the solidification of the Canadian national ethos, making locality and globality go hand in hand. Negotiating the meaning of regional identities is therefore a consequence of the processes of globalisation, which have been affecting how we (de)construct the nation. This paper addresses how a vested representation in fiction from the Canadian west and the prairies helped keep at bay the spectrum of fragmentation that threatened the hermetic body of a national literature and culture. Whereas traditional patterns of history and fiction have constructed the west under a recurrent attention to ossified issues of landscape, the west and the plains were more recently conceptualized in attention to a different tackling of time / space: one that unified the former prairies and the west in just one single experience. Anticipating much of the theoretical approach to the global through locality launched in the early 21st century, while also being inheritors of previous theoretical and fictional attempts at renewing regional myths, Guy Vanderhaege’s The Englishman’s Boy (1996) and Thomas Wharton’s Icefields (1997) make the structuring potential of their times and spaces lose their hegemony, thus favouring the rooting of postmodern myths and ineffability to unmark the borders of region, and destabilize those of the national discourse.